2014
DOI: 10.1007/s13364-014-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Does land use within the home range drive the exposure of roe deer (Capreolus capreolus) to two abortive pathogens in a rural agro-ecosystem?

Abstract: The recent increase in interactions between wildlife and domestic animals has heightened the risks of transmission of pathogens between wildlife, livestock, and humans. Our objective was to better understand how the spatial behavior of wildlife impacts their exposure to pathogens. We carried out a 5-year serological survey of Toxoplasma gondii and Chlamydia abortus in a roe deer population (Capreolus capreolus) living in a rural landscape and monitored using GPS technology. We tested whether the apparent serop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…The most common was MAT, used in 6/10 studies in roe deer and 4/8 in red deer. Only two studies reported the sensitivity and specificity of the serological test used; one in roe deer (Sevila et al., 2014) and one in red deer (Formenti et al., 2015). As regards the sample tested, all the studies used serum, with the exception of Rocchigiani et al., (2016) and Witkowski et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common was MAT, used in 6/10 studies in roe deer and 4/8 in red deer. Only two studies reported the sensitivity and specificity of the serological test used; one in roe deer (Sevila et al., 2014) and one in red deer (Formenti et al., 2015). As regards the sample tested, all the studies used serum, with the exception of Rocchigiani et al., (2016) and Witkowski et al.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of animals tested was 3,913 for roe deer and 2,913 for red deer. As shown in Tables 3 and 4, deer (Sevila et al, 2014) and one in red deer (Formenti et al, 2015).…”
Section: Study Selectionmentioning
confidence: 92%
See 1 more Smart Citation
“…They have a higher body mass than forest individuals (Hewison et al ., 2009). However, they can also be more exposed to parasites hosted by domestic species, such as oocysts of Toxoplasma gondii excreted by cats (Sevila et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sporulation of oocysts is inhibited below −6 °C (Dumètre and Dardé, 2003), but at 25 °C they remain viable in water for over 200 days (Dubey, 1998). Generally, infection of wildlife is associated with mild, moist environments experiencing infrequent periods of freezing (Dubey and Beattie, 1988; Afonso et al 2013; Sevila et al 2014).…”
Section: Introductionmentioning
confidence: 99%